MANAGING SUSTAINABLE FOREST RESOURCES AND CREATIVE ECONOMY THROUGH PARTNERSHIP STRATEGY AMONG STAKEHOLDER IN JAVA FOREST, INDONESIAN - H, Rachmat Pudjo; Kartini, Hj. Dwi; Kaltum, Hj. Umi, Hilmiana (CENTRAL ASIA AND THE CAUCASUS, 2022)
Forest governance to ensure sustainability requires a support system that is developed based on the consideration of the interaction and exchange of values between stakeholders. The research objective is to analyze Managing sustainable forest resources and creative economy through partnership strategy among stakeholders in Java Forest Indonesian. The research method uses an inferential survey approach to the partnership between forest stakeholders and the Forest Village Community Institution (LMDH). The number of forest stakeholder units is 57 that have LMDH partners with observation units involving the leaders of forest stakeholders and LMDH units. The results of the study show that efforts to ensure the sustainability of forest resources cannot be separated from the interaction of social exchanges with the surrounding community. These interactions provide access for the community to participate in managing resources, gain value and contribute to maintaining these resources. Interaction with LMDH as an institutionalized process as an important part of FMUs in implementing forest resource management. The partnership has developed into a system that encourages creative economic activity in the community. Partnership as a system developed and built to support the sustainability of forest resources and create a developing creative economy. The theoretical implication is that forest governance cannot ignore the function of partnerships as a dynamic system. Partnership as a strategy to ensure sustainability of forest resources and create a creative economy Forest Village Community Institution (LMDH).